Conquering the Rock—A Retrospective Single-Center Experience of the Transapical Petrosal Transtentorial (Kawase) Approach: Operative Technique and Impact on Cranial Nerve Function - Volovici, V.; Dammers, R.; Dirven, C. M. F.; Delwel, E. J. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Since its description in 1985, the transapical petrosal transtentorial or Kawase approach has become a viable option of approaching lesions located in and around the apex of the petrous bone, Meckel's cave, and the anterolateral surface of the brain stem while preserving cranial nerve function. At the Brain Tumor Center, Erasmus MC, 25 patients were treated using the Kawase approach between 2004 and 2018 for various indications, including petroclival meningiomas, chondrosarcomas, pontine cavernomas, trigeminal schwannomas, and posterior circulation aneurysms. Hearing preservation was achieved in all patients; new abducens nerve and trochlear nerve palsies were present in three and six patients, respectively, of which a total of eight required ophthalmological correction. Seven patients experienced a cerebrospinal fluid fistula postoperatively, but this complication appeared self-limiting in all cases, with one patient experiencing secondary meningitis. After modifying our closure technique, the rate of fistulas dropped to zero. The observed direct postoperative mortality was 4% (one patient), although not related to the approach itself. In conclusion, the Kawase approach is a highly complex, but essential middle fossa approach, extremely robust, and able to serve a wide array of pathologies together with its extensions. It is very accurate for performing hearing preservation surgery, but not without caveats and inherent risk of complications.
Keywords: petrosectomy; petroclival meningioma; Kawase approach; cranial nerve; anterior